Pengaruh Gratis Ongkir, Online Costumer Review Dan Flash Sale Terhadap Keputusan Pembelian Marketplace Tiktok Shop (Studi Pengguna Tiktok Shop di Kota Malang) - Fayadl, Moh Fali; Widarko, Agus; Mustapita, Arini Fitria (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze and describe the influence of free shipping, online customer reviews and flash sales on purchasing decisions on the TikTok Shop marketplace (case study of TikTok Shop marketplace users in Malang City). The population in this study were consumers in Malang who had purchased at the Tiktok Shop. Determining the number of samples used the Malhotra formula and the results obtained were 95 respondents. Data collection was carried out using a questionnaire. To solve the problem in this research using SPSS assistance with the analytical methods used in this research are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, t test, coefficient of determination test (R2) . The research results of online customer reviews have a significant effect on purchasing decisions, while free shipping and flash sales do not have a significant effect on purchasing decisions. Keywords: Free Shipping, Online Customer Reviews, Flash Sales, And Purchasing Decisions.